The Intersection of Chronic Obstructive Pulmonary Disease and Cardiovascular Disease: Recent Insights in a Challenging Area - Michael Heffernan, MD, PhD, FRCPC, FACC; Samantha Rutherford, BHSc (CJC Open)
Chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD) are 2 prevalent and interconnected health conditions that have a significant global impact. COPD is characterized by airflow obstruction and is caused by smoking and/or environmental factors. COPD is associated with chronic inflammation and structural changes in the airways and lung parenchyma. CVD encompasses various cardiac and vascular conditions and is a leading global cause of mortality, with risk factors that include diabetes, smoking, and dyslipidemia. CVDs discussed in this review, in relation to COPD, include hypertension, coronary artery disease and ischemic heart disease, heart failure, cardiac arrhythmias, and cerebrovascular disease. The interplay between COPD and CVD is evident, with shared risk factors and physiological mechanisms contributing to their frequent comorbidity. Therefore, an integrated approach to care involving primary care physicians, respirologists, and cardiologists is essential to effectively manage the dual burden of COPD and CVD.This review outlines the shared risks and underlying mechanisms of these conditions, their diagnosis, and the clinical implications of dual COPD and CVD in a patient, including how COPD exacerbations significantly elevate the risk of cardiovascular (CV) events and mortality. Pharmacologic CVD and COPD therapies, as well as their CV and respiratory effects, are discussed. Key trials (Towards a Revolution in COPD Health [TORCH]; Study to Understand Mortality and Morbidity in COPD [SUMMIT]; InforMing the Pathway of COPD Treatment [IMPACT]; and Efficacy and Safety of Triple Therapy in Obstructive Lung Disease [ETHOS]) are discussed that demonstrate the effectiveness of triple bronchodilator therapy in reducing exacerbation rates, as well as all-cause and cardiovascular mortality in patients with COPD and CVD. Overall, this review highlights the need for an integrated approach to patient management, involving collaboration among primary care physicians, respirologists, and cardiologists, to effectively address the dual burden of these diseases. Résumé: La bronchopneumopathie chronique obstructive (BPCO) et les maladies cardiovasculaires (MCV) sont deux problèmes de santé prévalents et interconnectés qui ont un impact mondial important. La BPCO se caractérise par une obstruction des voies aériennes et est causée par le tabagisme et/ou des facteurs environnementaux. La BPCO est associée à une inflammation chronique et à des modifications structurelles des voies respiratoires et du parenchyme pulmonaire. Les MCV englobent diverses affections cardiaques et vasculaires et constituent l'une des principales causes de mortalité dans le monde, avec des facteurs de risque tels que le diabète, le tabagisme et la dyslipidémie. Les MCV abordées dans cette revue de littérature, en relation avec la BPCO, comprennent l'hypertension, la maladie coronarienne et la cardiopathie ischémique, l'insuffisance cardiaque, les arythmies cardiaques et les maladies cérébrovasculaires. L'interaction entre la BPCO et les MCV est évidente, les facteurs de risque et les mécanismes physiologiques communs contribuant à leur fréquente comorbidité. Par conséquent, une approche intégrée des soins impliquant les médecins de soins primaires, les pneumologues et les cardiologues est essentielle pour gérer efficacement le fardeau partagé de la BPCO et des MCV.Cette revue décrit les risques partagés et les mécanismes sous-jacents de ces pathologies, leur diagnostic et les implications cliniques de la double présence de BPCO et MCV chez le patient, y compris la façon dont les exacerbations de la BPCO augmentent de manière significative le risque d'événements cardiovasculaires (CV) et de mortalité. Les traitements pharmacologiques des MCV et de la BPCO, ainsi que leurs effets CV et respiratoires, sont abordés. Des essais clés (Towards a Revolution in COPD Health [TORCH]; Study to Understand Mortality and Morbidity in COPD [SUMMIT]; InforMing the Pathway of COPD Treatment [IMPACT]; et Efficacy and Safety of Triple Therapy in Obstructive Lung Disease [ETHOS]) sont évoqués, qui démontrent l'efficacité de la trithérapie bronchodilatatrice dans la réduction des taux d'exacerbation, ainsi que de la mortalité cardiovasculaire et toutes causes confondues, chez les patients atteints de BPCO et de MCV. Dans l'ensemble, cette revue souligne la nécessité d'une approche intégrée de la prise en charge des patients, impliquant une collaboration entre les médecins de soins primaires, les pneumologues et les cardiologues, afin de traiter efficacement la double problématique de ces pathologies.